Construction of Various Bridged Polycyclic Skeletons by Palladium‐Catalyzed Dearomatization - Mu, Xingye; Yu, Hanxiao; Peng, Henian; Xiong, Wenrui; Wu, Ting; Tang, Wenjun (Angewandte Chemie International Edition, 2020)
A powerful palladium‐catalyzed dearomative cyclization was developed that provides facile access to eight types of bridged tetracyclic skeletons bearing various ring sizes and heterocycles. With this method, several skeletons or analogues of natural products, including tubingensin B and dracaenones, were synthesized. Asymmetric dearomative cyclization enables the construction of various enantiomerically enriched bridged polycyclic systems with up to 99 % ee by employing a chiral palladium catalyst. Give me a ring: A palladium‐catalyzed dearomative cyclization was developed that provides facile access to eight types of bridged tetracyclic skeletons bearing various ring sizes and heterocycles. Several skeletons or analogues of natural products, including tubingensin B and dracaenones, were synthesized. Asymmetric dearomative cyclization with a chiral palladium catalyst provided enantiomerically enriched bridged polycyclic systems with up to 99 % ee.